The Nasal Route as a Potential Pathway for Delivery of Erythropoietin in the Treatment of Acute Ischemic Stroke in Humans - Julio Cesar García-Rodríguez; Iliana Sosa Teste (The Scientific World Journal)
Intranasal delivery provides a practical, noninvasive method of bypassing the blood-brain barrier (BBB) in order to deliver therapeutic agents to the brain. This method allows drugs that do not cross the BBB to be delivered to the central nervous system in a few minutes. With this technology, it will be possible to eliminate systemic administration and its potential side effects. Using the intranasal delivery system, researchers have demonstrated neuroprotective effects in different animal models of stroke using erythropoietin (EPO) as a neuroprotector or other different types of EPO without erythropoiesis-stimulating activity. These new molecules retain their ability to protect neural tissue against injury and they include Asialoerythropoietin (asialoEPO) carbamylated EPO (CEPO), and rHu-EPO with low sialic acid content (Neuro-EPO). Contrary to the other EPO variants, Neuro-EPO is not chemically modified, making it biologically similar to endogenous EPO, with the advantage of less adverse reactions when this molecule is applied chronically. This constitutes a potential benefit of Neuro-EPO over other variants of EPO for the chronic treatment of neurodegenerative illnesses. Nasal administration of EPO is a potential, novel, neurotherapeutic approach. However, it will be necessary to initiate clinical trials in stroke patients using intranasal delivery in order to obtain the clinical evidence of its neuroprotectant capacity in the treatment of patients with acute stroke and other neurodegenerative disorders. This new therapeutic approach could revolutionize the treatment of neurodegenerative disorders in the 21st century.